(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To assess the risk of pressure ulcers in bedridden individuals assisted by the Family Health Strategy. Method: A cross-sectional study employing a quantitative approach was conducted with 62 patients. Data collection was performed through a semi-structured questionnaire, encompassing sociodemographic and clinical data, as well as the assessment of pressure ulcer risk using the Braden Scale. Data were analyzed using the Statistical Package for the Social Sciences software, version 20.0. Results: Female patients (61.3%), Caucasians (43.5%), widows (35.5%), married individuals (66.1%), and those with no formal education (62.9%) predominated. The primary reason for being bedridden was sequelae from a stroke (35.5%). A prevalence of very high risk was observed in 59.7% of bedridden individuals. Conclusion: The risk of pressure ulcers was high, emphasizing the necessity of identifying risk factors to inform preventive or mitigating strategies for this condition.